Karyotype analysis in Brachiaria (Poaceae) species - Bernini, C.; Marin-Morales, M. A. (Faculty Press, 2001)
This is the first karyotype characterization of Brachiaria species. Twelve accessions belonging to five species were analysed. The basic chromosome number was x = 9 and 7, the same reported for the tribe Paniceae. Variations in the chromosome number were observed in B. decumbens (2n = 18; 36) and B. humidicola (20 = 36; 42; 54). Chromosome numbers of 20 = 18 in B. ruziziensis and 20 = 36 in B. brizantha and B. jubata were recorded. Inter- and intraspecific karyotype differentiation of the accessions analysed was facilitated by variations in karyotypic symmetry. The karyotypes were generally considered symmetrical, with a tendency to asymmetry in the direction of the polyploids. It is suggested that addition, deletions and mainly polyploidy have been the most direct causes involved in the chromosome evolution of this genus.
Keywords: chromosome; karyotype; Brachiaria; cytogenetics